Excavations at Myrmekion in 2019–2023 - Butyagin, Alexander; Kolosov, Vladimir; Giblova, Anastasiya; Milikhina, Nadezhda (Hyperboreus, 2024)
From 2019 to 2023, excavations at the Myrmekion settlement site were conducted in three main areas: the central (I), the western (TS), and the eastern (M). Within the area M, a necropolis from the second half of the 6th century BC was discovered, as well as a section of a defensive wall with a gate and a paved street leading to it. The construction of the wall dates back to the turn of the 3rd to the 2nd centuries BC, judging from the found materials. A fragmentary tombstone stele with the inscription Περίανδρος Μύρμηκος [dotted kappa] was found near a Roman era pit. At the site I during the study of a house from the first centuries AD and layers of the Hellenistic Ash-Hill II, fragments of two lead letters were found. In addition, a hoard of 30 gold staters of the Alexander the Great type, dating back to the late 4th century BC, was found in a ceramic vessel. Excavations in the TS area have been continued to uncover estates of the 1st to 3rd centuries AD. A Late Bronze Age grave was also found under one of the Roman era walls. An area to the northeast of the settlement with a layer from the 4th century BC was studied, as well.